Antioxidant and cytotoxic activity of propolis of Plebeia droryana and Apis mellifera (Hymenoptera, Apidae) from the Brazilian Cerrado biome. - Thaliny Bonamigo; Jaqueline Ferreira Campos; Alex Santos Oliveira; Heron Fernandes Vieira Torquato; José Benedito Perrella Balestieri; Claudia Andrea Lima Cardoso; Edgar Julian Paredes-Gamero; Kely de Picoli Souza; Edson Lucas Dos Santos (PLoS ONE, 2017)
Propolis is a complex bioactive mixture produced by bees, known to have different biological activities, especially in countries where there is a rich biodiversity of plant species. The objective of this study was to determine the chemical composition and evaluate the antioxidant and cytotoxic properties of Brazilian propolis from the species Plebeia droryana and Apis mellifera found in Mato Grosso do Sul, Brazil. In the ethanolic extracts of P. droryana propolis (ExEP-P) and A. mellifera (ExEP-A) acids, phenolic compounds, terpenes and tocopherol were identified as major compounds. Both extracts presented antioxidant activity against the 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical, the maximum activities being 500 μg/mL (ExEP-P) and 300 μg/mL (ExEP-A). However, only ExEP-A was able to inhibit lipid peroxidation induced by the oxidizing agent 2,2'-azobis(2-amidinopropane) dihydrochloride (AAPH), which inhibited oxidative hemolysis and reduced the levels of malondialdehyde (MDA) in human erythrocytes for 4 h of incubation. The extracts also reduced the cell viability of the K562 erythroleukemia tumour line, with a predominance of necrotic death. Thus, it is concluded that the propolis produced by P. droryana and A. mellifera contain important compounds capable of minimizing the action of oxidizing substances in the organism and reducing the viability of erythroleukemia cells.